2012
DOI: 10.1080/13032917.2012.687690
|View full text |Cite
|
Sign up to set email alerts
|

The effects of marketing communication on the tourist's hotel reservation process

Abstract: The paper analyses the tourist's first stay booking decision and the factors (such as advertising, word-of-mouth, and travel agency recommendation) that most significantly influence it. Three research hypotheses have been considered and a logistic regression model has been specified. The factors "advertising" and "word-ofmouth" have significant power to explain direct-contact booking. Hence, there is not only a strong association between first stay booking and the Web, but also a very strong association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…These results are in line with results from [34] who conducted a quantitative study on effects of communication on tourists' hotels reservation process and concluded that there is strong relationship between marketing and hotel reservations.…”
Section: Table 5: Brand Consultationsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are in line with results from [34] who conducted a quantitative study on effects of communication on tourists' hotels reservation process and concluded that there is strong relationship between marketing and hotel reservations.…”
Section: Table 5: Brand Consultationsupporting
confidence: 81%
“…Unsatisfied customers are not good for both destination marketing organisation and destination stakeholders as it limits repeat business and ability to convince future clients of your products and services. These results are in line with results by [34] who conducted a quantitative study on effects of communication on tourists' hotels reservation process and concluded that there is a strong relationship between marketing and hotel reservations. Thus a holistic approach is ideal in trying to create a realistic brand that is appealing to the clients and can be satisfied by the stakeholders on the ground when the tourists visit the destination.…”
Section: Stakeholder Consultation On (Re)brandingsupporting
confidence: 80%
“…Nowadays, a majority of hotels and airlines depend heavily on websites for direct bookings, either their own website or the websites of travel agencies. It is highly crucial that these organizations make sure that they provide the latest information and offer attractive deals for customers (Almeida, Silva, Mendes, & Oom do Valle, 2012).…”
Section: E-bookingmentioning
confidence: 99%
“…A method called KASR (Keyword Aware Service Recommendation) has been proposed for the big data analysis of reviews by Meng et al [18]. In a big data environment, KASR has been implemented in Hadoop and cloud for the sake of improving the efficiency and the scalability in the environment of big data [20,21].…”
Section: Recommender Systemsmentioning
confidence: 99%